Impact of consistent government's renewable energy policies on private investment towards renewable energy - HWANG, Geum-mul-gyul (KDI School, 2017)
The study aims to empirically investigate the impact of implementing time-consistent policy on private investment in renewable energy infrastructure in developing countries, while the other independent variables are controlled. Data set of renewable energy PPP project in 16 developing countries between 2005 and 2014 was used in the study while project characteristics, political risk, civil risk and aid were controlled. The study proved that once the renewable energy policy is time-consistent in terms of providing economic incentive to private sector, private investment dramatically increases. The policy recommendation by this study is to establish an umbrella body to resolve asymmetric information problem between government and private sector. This will help private sector more responsive to unexpected policy change. More importantly, policy makers in developing countries should keep in mind value of consistency by making long-term commitment to achieve policy goal. By doing so, policy makers are able to draw relatively accurate blueprint of how government renewable energy policy should be developed
Thesis(Master) --KDI School:Master of Development Policy,2017